Plant Species In The Honggoderpo Cemetery, Wonosobo Regency, Central Java - Irsyam, Arifin Surya Dwipa; Ristiawan, Hani; Hariri, Muhammad Rifqi; Peniwidiyanti, Peniwidiyanti; Irwanto, Rina Ratnasih (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2022)
Honggoderpo Cemetery is one of the urban green open spaces (RTH) which is located adjacent to the center of Wonosobo Regency, Central Java. This cemetery is a sacred area, so disturbances to the environment are rare, including plants. Therefore, plant diversity is still maintained...